Determinants of the Trade Balance in Industrialized Countries - Martin Falk (FIW - Research Centre International Economics, 2008)
This paper investigates the determinants of the trade balance using panel data for 32 industrialized and emerging economies for the period 1990?2007. The results based on fixed effects models and linear mixed models allowing for random slope coefficients, show that the trade balance as a percentage of GDP is significantly positively related to real foreign GDP per capita of the trading partners. Real domestic GDP per capita has a negative effect on the trade balance. A real depreciation of the real exchange rate index leads to an improvement of the trade balance. However, in countries with a negative trade balance and/or a large positive net foreign direct investment position the trade balance is much less sensitive to movements in the real effective exchange rate index.
Keywords: F10; F31; 330; Foreign Direct Investment; trade balance; real effective exchange rate index; fiscal balance; panel data methods